2023
DOI: 10.3390/app13095420
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Muscle and Medial Retinaculum Combinate Effects on Patellar Instability during Knee Flexion

Abstract: Background: Patellar instability can cause pain and disability. A finite element model of a healthy human knee was performed to analyze the role of quadriceps and medial retinaculum imbalance in patellar instability. Methods: The model was created by matching magnetic resonance and computed tomography images of a normal adult patient’s knee. Muscle force intensities were calculated by static optimization, considering the lower limb muscles, knee movement and the ground reaction during walking. Patellar instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…The aim of the present research was to estimate stress distribution occurring in a clavicle fracture surgically treated with a plate, compared to a healthy one, during elevation of the shoulder. Numerous previous studies have used FE analysis to gain a better understanding of the disease consequences in terms of timing, outcomes, and healthcare costs [35,[42][43][44]. Several authors have demonstrated improved early functional outcomes with lower rates of nonunion and symptomatic aesthetic deformity with surgical treatment of clavicle fractures compared to non-surgical treatment [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present research was to estimate stress distribution occurring in a clavicle fracture surgically treated with a plate, compared to a healthy one, during elevation of the shoulder. Numerous previous studies have used FE analysis to gain a better understanding of the disease consequences in terms of timing, outcomes, and healthcare costs [35,[42][43][44]. Several authors have demonstrated improved early functional outcomes with lower rates of nonunion and symptomatic aesthetic deformity with surgical treatment of clavicle fractures compared to non-surgical treatment [45,46].…”
Section: Discussionmentioning
confidence: 99%